2018
DOI: 10.3389/fnins.2018.00397
|View full text |Cite
|
Sign up to set email alerts
|

Plin4-Dependent Lipid Droplets Hamper Neuronal Mitophagy in the MPTP/p-Induced Mouse Model of Parkinson’s Disease

Abstract: Epidemiological studies have shown that both lipid metabolism disorder and mitochondrial dysfunction are correlated with the pathogenesis of neurodegenerative diseases (NDDs), including Parkinson’s disease (PD). Emerging evidence suggests that deposition of intracellular lipid droplets (LDs) participates in lipotoxicity and precedes neurodegeneration. Perilipin family members were recognized to facilitate LD movement and cellular signaling interactions. However, the direct interaction between Perilipin-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 40 publications
(69 reference statements)
2
65
0
Order By: Relevance
“…61 However, little is currently known about the specific function of PLIN3 in beta cells. 144 There currently is little information regarding the role of PLIN4 in beta cells. PLIN4 has three times larger molecular weight compared with other PLINs, and the least studied among PLINs in nonbeta cells.…”
Section: Plin2 the Most Abundant Plin In Beta Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 However, little is currently known about the specific function of PLIN3 in beta cells. 144 There currently is little information regarding the role of PLIN4 in beta cells. PLIN4 has three times larger molecular weight compared with other PLINs, and the least studied among PLINs in nonbeta cells.…”
Section: Plin2 the Most Abundant Plin In Beta Cellsmentioning
confidence: 99%
“…143 Recently, PLIN4 was found to inhibit mitophagy in a neuroblastoma cell line. 144 There currently is little information regarding the role of PLIN4 in beta cells. Of note, the expression of PLIN4 in beta cells and pancreatic islets is very low (Fig.…”
Section: Plin5 a Potential Regulator Of Lipolysis In Beta Cellsmentioning
confidence: 99%
“…It is upregulated during systemic inflammation (Kang et al 2017) and has been found to be elevated in the brains of AD patients (Naudé et al 2012). Plin4 is often associated with triacylglycerol metabolism and is involved in the biogenesis of lipid droplets in pathological degeneration (Han et al 2018). The PolyI:C model shows a strong and specific rise in lipid droplets density accompanied by an increase in Lcn2 protein levels in neurons and glia, which confirms the metabolic and inflammatory disbalance in response to systemic immune challenge.…”
Section: Genetic Remodelingmentioning
confidence: 87%
“…5F). (II) On the other hand, genes related to neuroinflammation such as the lipiddroplet dependent gene (Plin4; Perilipin 4) (Han et al 2018), pro-inflammatory genes (H2-Aa; Immunohistocompatibility-complex) (Van Hove et al 2019) and acute-phase proteins regulating to the inflammatory response (Lcn2; Lipocalin-2) (Dekens et al 2020) are upregulated in aging PP mice, starting from 9 months (Fig. 5G).…”
Section: Dynamic Remodeling Of the Hippocampal Transcriptomementioning
confidence: 97%
“…Several studies have reported that expression of human Syn dysregulates TG metabolism and LD homeostasis in cellular and rodent models of PD (Cole et al, 2002;Fanning et al, 2019;Han et al, 2018;Outeiro and Lindquist, 2003;Sánchez Campos et al, 2018). As noted above, LD homeostasis crucially relies on peridroplet proteins.…”
Section: Syn Synergizes With Plin Proteins To Induce Ld Accumulationmentioning
confidence: 99%